Genetic diversity of highly pathogenic avian influenza H5N6 and H5N8 viruses in poultry markets in Guangdong, China, 2020-2022 - Yang, Kang; Nizami, Sarea; Hu, Shu; Zou, Lirong; Deng, Huishi; Xie, Jiamin; Guo, Qianfang; Edwards, Kimberly M.; Dhanasekaran, Vijaykrishna; Yen, Hui-Ling; Wu, Jie (Journal of virology, 2025)
Since 2016/2017, clade 2.3.4.4b H5Nx viruses have spread via migratory birds to all continents except Oceania. Here, we evaluated the impact of the re-introduction of clade of 2.3.4.4b on highly pathogenic avian influenza (HPAI) virus genetic diversity in China. Twenty-two H5N6 and H5N8 HPAI isolated from monthly surveillance in two poultry markets in Guangdong between 2020 and 2022 were characterized. Our findings showed that clade 2.3.4.4h, detected in 2020, was replaced by clade 2.3.4.4b in 2021–2022. H5N6 ( n = 18) were clustered into more genotypes than H5N8 ( n = 4), suggesting that H5N6 may possess better replication fitness in poultry. Conversely, the H5N8 genotypes are largely derived from the clade 2.3.4.4b wild bird isolates. As clade 2.3.4.4b continues to spread via migratory birds, it is anticipated that the genetic diversity of H5N6 viruses circulating in China may continue to expand in the coming years. Continuous efforts in surveillance, genetic analysis, and risk assessment are therefore crucial for pandemic preparedness.